Perbedaan Asupan Zat Besi dan Vitamin A Baduta (Bawah Dua Tahun) Sebelum dan Sesudah Edukasi Menggunakan Media “Puzzle Isi Piring Baduta” - Mutiarani, Anugrah Linda; Wulandari, Catur; Dwijayanti, Ira; Isyrofi, Atik Qurrota A'yunin Al (Media Gizi Kesmas, 2024)
Background: Iron and vitamin A are important micronutrients for under two years old. Iron deficiency and vitamin A deficiency can cause nutritional problems related to underweight and stunting. Providing a variety of food according to the contents of my plate is one effort to fulfill these nutrients. Mother’s knowledge, attitudes, and behavior influence baby-feeding practices. Objectives: Analyzing differences in under two years old’s iron and vitamin A intake before and after education using the “under two years old’s plate content puzzle” Methods: This type of research used quantitative with a pre-experimental research and one-group pretest-posttest design. The total sample was 67 mothers under two years old in 08 Sub-Village, Keputih Subdistrict, Surabaya City. The sampling method used was total sampling. Collecting data on the nutritional intake of under two years old used 2x24-hour recall. The statistical test used the Wilcoxon sign rank test to see differences in intake.  Results: The study showed a significant difference before and after education in iron and vitamin A intake in under two years old with a p-value=0,000. Conclusions: Education used media “puzzle isi piring baduta” has an effect on iron and vitamin A intake under two years old.